Seasonal denning behavior and population dynamics of the late Pleistocene peccary Platygonus compressus (Artiodactyla: Tayassuidae) from Bat Cave, Missouri - Woodruff,Aaron L.; Schubert,Blaine W. (PeerJ, 2019)
The late Pleistocene faunal assemblage from Bat Cave, central Ozarks, Missouri provides an opportunity to assess specific aspects of behavior, ecology, and ontogeny of the Rancholabrean species Platygonus compressus. All identifiable elements referable to this taxon were catalogued and examined, and a minimum number of individuals of 73 was determined for the sample. Evidence of seasonal behavioral patterns are reported for the first time in a fossil peccary. Maturation of individuals was assessed using the tooth eruption sequence and occlusal wear patterns for all tooth-bearing mandibular elements and isolated lower dentition. Approximate ages were established through comparison with the extant collared peccary. The presence of distinct, developmentally non-overlapping age groups suggests that P. compressus was seasonally present at the Bat Cave locality, with the cave functioning as seasonal shelter in which individuals would occasionally die. The study also suggests the peccaries engaged in synchronous, seasonal breeding behaviors. Demographic assessment of the Bat Cave peccary population suggests that younger individuals formed the bulk of the population at a given time with progressively older individuals becoming scarcer until the age of about 10 years, which matches the typical demographic patterns and life expectancy of extant peccaries.
Keywords: Tayassuidae; Paleoecology; Pleistocene; Demography; Platygonus compressus; Denning